Peran Pembiayaan Dan Bimbingan Kepada Usaha Mikro Kecil Dan Menengah (UMKM) Sebagai Solusi Dalam Meningkatkan Produktivitas Usaha Pada UMKM Kota Medan - Romi Alhadid Rangkuti; Sri Ramadhani (Universitas Labuhanbatu, 2022)
The problems faced by MSMEs are quite complex, namely the low productivity of MSMEs caused by the low quality of human resources of MSMEs, especially in the field of Management, Mastery of technology, and marketing. In addition, MSMEs are also faced with limited access to productive resources, especially to capital, technology, information and markets. Lack of capital of MSMEs, because in general, small and medium enterprises are private businesses or companies that are closed, which rely on capital from owners of very limited amounts, while loan capital from banks or other financial institutions is difficult to obtain, because the administrative and technical requirements requested by banks cannot be met. Community service activities carried out to increase awareness of MSMEs related to financing problems and maximize the productivity of MSMEs activities by taking advantage of opportunities for bank credit facilities, cooperative assistance, and 3rd party funding providers in helping develop MSMEs to increase and maximize Small Business Loans which is a solution to the problem of financing MSMEs to develop and advance. Responding to the cooperation of MSMEs in preparing short-term business planning, preparation of business development proposals as well as facilities and mediation of access to financial institutions and various financing sources and financial management carried out with MSMEs at the time of this technical guidance.